Microwave Ablation Compared With Laser Ablation for Treating Benign Thyroid Nodules in a Propensity-Score Matching Study - Shi, Yi-Fan; Zhou, Ping; Zhao, Yong-Feng; Liu, Wen-Gang; Tian, Shuang-Ming; Liang, Yong-Ping (Frontiers in Endocrinology, 2019)
Objective: The efficacy and safety of percutaneous ultrasound-guided microwave and laser ablation (MWA and LA, respectively), for treating benign thyroid nodules (BTNs), were retrospectively compared. Methods: Patients (n = 318) underwent ablation of 328 BTNs. Confounding bias was reduced by propensity-score matching, and finally the MWA and LA groups each comprised 160 nodules. At baseline (before ablation), 3, 6, and 12 months, and every 6 months thereafter, the following were recorded: nodule volume reduction rate (VRR), neck symptom scores, cosmetic scores, complications, and side effects. Results: The baseline characteristics of the MWA and LA groups were comparable. The volumes of all nodules were less at all follow-ups relative to the baseline, as were the symptom and cosmetic scores at postoperative 6 months and thereafter (P < 0.01). At each follow-up, the overall VRRs of the MWA and LA groups were comparable. However, for nodules ≥13 mL, the VRR associated with LA at ≥6 months was significantly greater than that of MWA. The average ablation time for MWA was less than that of LA (P < 0.01). The overall incidences of major complications, minor complications, and side effects were 1.6, 2.2, and 18.4%, respectively, and there were no significant differences between the MWA and LA groups. Conclusion: Percutaneous ultrasound-guided MWA and LA are both safe and effective for the treatment of BTNs. Each can significantly reduce the nodule volume and improve the neck symptoms and appearance of patients, with a low incidence of adverse side effects. The efficiency of MWA is higher than that of LA. For nodules ≥13 mL, MWA may be preferred, but at 6 months and subsequent follow-ups the reduction in volume was greater in patients receiving LA.